Social media and depression symptoms: A network perspective - Aalbers, George; McNally, Richard J; Heeren, Alexandre; de Wit, Sanne; Fried, Eiko I (Journal of experimental psychology. General, 2019)
Passive social media use (PSMU)-for example, scrolling through social media news feeds-has been associated with depression symptoms. It is unclear, however, if PSMU causes depression symptoms or vice versa. In this study, 125 students reported PSMU, depression symptoms, and stress 7 times daily for 14 days. We used multilevel vector autoregressive time-series models to estimate (a) contemporaneous, (b) temporal, and (c) between-subjects associations among these variables. (a) More time spent on PSMU was associated with higher levels of interest loss, concentration problems, fatigue, and loneliness. (b) Fatigue and loneliness predicted PSMU across time, but PSMU predicted neither depression symptoms nor stress. (c) Mean PSMU levels were positively correlated with several depression symptoms (e.g., depressed mood and feeling inferior), but these associations disappeared when controlling for all other variables. Altogether, we identified complex relations between PSMU and specific depression symptoms that warrant further research into potentially causal relationships. (PsycINFO Database Record (c) 2019 APA, all rights reserved).